Diffuse Hot Plasma in the Interstellar Medium and Galactic Outflows - Sasaki, Manami; Ponti, Gabriele; Mackey, Jonathan (Springer Nature, 2024)
We summarize observations and our current understanding of the interstellar medium (ISM) in galaxies, which mainly consists of three phases: cold atomic or molecular gas and clouds, warm neutral or ionized gas, and hot ionized gas. These three gas phases form thermally stable states, while disturbances are caused by gravitation and stellar feedback in the form of photons and shocks in stellar winds and supernovae. Hot plasma is mainly found in stellar bubbles, superbubbles, and Galactic outflows/fountains and is often dynamically unstable and is overpressurized. In addition, in Galactic nuclear regions, accretion onto the supermassive black hole causes enhanced star formation, outflows, additional heating, and acceleration of cosmic rays.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Galactic center; Galactic outflows; Galactic ridge; Interstellar medium; Star formation; Stellar bubbles; Stellar winds; Superbubbles; Supernova remnants